Who is the Other in the age of the Anthropocene? Introducing the Unknown Other in climate justice discourse. (April 2019) - Antadze, Nino
This paper contributes to advancing the research agenda on ethics in the Anthropocene (Schmidt JJ, Brown PG and Orr CJ (2016) Ethics in the Anthropocene: A research agenda. The Anthropocene Review 3(3): 188–200). Specifically, it responds to the call to explore 'the new human condition' (Palsson G, Szerszynski B, Sörlin S et al. (2013) Reconceptualizing the 'Anthropos' in the Anthropocene: Integrating the social sciences and humanities in global environmental change research. Environmental Science & Policy 28: 8) in the age of the Anthropocene by rethinking the relational ontology within the context of climate change. I propose that given the global and long-term implications of climate change, climate justice discourse should go beyond the Self–Other binary and incorporate the notion of the Unknown Other. By drawing on the moral philosophy of Emmanuel Levinas and moral sentimentalism scholarship, I theorize the ethical relationship with the Unknown Other. I propose that the encounter with the 'face' (identity, experience, voice) of the Unknown Other is conditioned by the Self's contribution to climate change. Therefore, the encounter with the Unknown Other is not physical and corporeal but ethical, and thus triggers a moral engagement that has a dual base – responsibility and emotion. The former is expressed in the form of asymmetrical responsibility and the latter in the form of empathy.